PENGARUH KONSENTRASI ION FE3+ YANG BERBEDA TERHADAP KANDUNGAN KLOROFIL a DAN b, KAROTENOID DAN ANTIOKSIDAN DARI Chlorella sp. - Dian Iriani; Bustari Hasan; Sumarto Sumarto (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
This research was aimed to determine the effect of iron (Fe3+) concentration on chlorophyll a and b content, carotenoid content and antioxidant capacity of Chlorella sp. The source of Fe3+ obtained from FeSO4.7H2O. The varying concentration of Fe3+ in Basal media was 0.35, 4.89, 9.44, and 13.99 mg/L. The harvesting of Chlorella sp. was conducted in 3 times: 7th day, 14th day, and 21st day of cultivation periode. The Chlorella sp. was harvested by centrifugation 4800 rpm for 10 minutes. Chlorophyll a b, and carotenoid content were determined by using spectrophotometer with absorbance (Abs) 480, 630, 645, 665 nm and antioxidant capacity was analysed using % DPPH scavenging capacity. Based on the research results shown that the highest amount of Chlorophyll a content (101.43 mg/L) and chlorophyll b content (49.25 mg/L) were resulted in the highest of Fe3+ concentration (13.99 mg/L) for 21 days of cultivation period, the highest carotenoid content (37.41 mg/L) was in 4.89 mg/L of Fe3+ concentration for 21 days of cultivation period, and the highest of % antioxidant capacity (32.74%) was in the lowest of Fe3+ concentration (0.35 mg/L) for 14 days of cultivation period.